The effect of e-waste in urban health: a systematic review - Pebriaini, Prisma Andita; Kurnia, Galuh Mega; Prasasti, Corie Indria (Universitas Gadjah Mada, 2025)
Purpose: E-waste is among the most rapidly increasing types of waste worldwide. This paper aims to systematise the existing literature and explore future research prospects on the effect of e-waste on urban health. Methods: This systematic review follows the Preferred Reporting Items for Systematic Reviews (PRISMA) guidelines. This literature search utilized articles available in the ScienceDirect, PubMed, and Google Scholar databases, published within the last ten years (2014-2024), to explore the relationship between e-waste and urban health. Results: E-Waste poses serious environmental and health risks, especially in areas with weak regulations and poor waste management. Exposure to hazardous substances through air, soil, and water, such as lead, mercury, and polycyclic aromatic hydrocarbons (PAHs), can lead to respiratory, cardiovascular, and neurodevelopmental issues. Informal recycling worsens these risks, particularly for workers and nearby communities. Weak enforcement, economic barriers, and low public awareness further exacerbate the problem. Effective mitigation includes extended producer responsibility (EPR), formal recycling systems, and a circular economy. Urgent action is needed through stronger policies, enforcement, and awareness; future research should focus on developing sustainable e-waste solutions. Conclusion: Our findings underscore the urgent need for integrated e-waste management policies and practices to safeguard urban public health and mitigate the adverse effects of e-waste exposure. This review lays the groundwork for future research aimed at understanding and addressing the complex health challenges posed by e-waste in urban environments.